2018
DOI: 10.4254/wjh.v10.i12.892
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved issues in the prophylaxis of bacterial infections in cirrhosis patients

Abstract: Bacterial infections are highly prevalent and a frequent cause of hospitalization and short-term mortality in patients with cirrhosis. Due to their negative impact on survival, antibiotic prophylaxis for bacterial infections in high-risk subgroups of patients with cirrhosis has been the standard of care for decades. Patients with prophylaxis indications include those at risk for a first episode of spontaneous bacterial peritonitis (SBP) due to a low ascitic fluid protein count and impaired liver and kidney fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, managing bacterial infections remains challenging, mainly due to the rise in multidrug-resistant organisms (MDRO), which contribute significantly to morbidity and short-term mortality. 1 Factors associated with MDRO infections in cirrhosis, such as MDRO colonisation, are of keen interest. 2 Yet, predicting MDRO colonisation is challenging, with few known associated variables beyond hospitalisation and antibiotic therapy.…”
Section: N V I T E D E D I T O R I a L Editorial: Terlipressin And Md...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, managing bacterial infections remains challenging, mainly due to the rise in multidrug-resistant organisms (MDRO), which contribute significantly to morbidity and short-term mortality. 1 Factors associated with MDRO infections in cirrhosis, such as MDRO colonisation, are of keen interest. 2 Yet, predicting MDRO colonisation is challenging, with few known associated variables beyond hospitalisation and antibiotic therapy.…”
Section: N V I T E D E D I T O R I a L Editorial: Terlipressin And Md...mentioning
confidence: 99%
“…In recent decades, there has been a notable progress in managing complications of cirrhosis, such as hepatorenal syndrome and variceal bleeding, leading to improvements in survival. However, managing bacterial infections remains challenging, mainly due to the rise in multidrug‐resistant organisms (MDRO), which contribute significantly to morbidity and short‐term mortality 1 . Factors associated with MDRO infections in cirrhosis, such as MDRO colonisation, are of keen interest 2 .…”
mentioning
confidence: 99%
“…On the other hand, Piano et al reported that antibiotics used prophylactically in patients with cirrhosis were not associated with the development of a resistance [ 18 ]. The issue of prophylactic antibiotic administration in patients with cirrhosis is unresolved [ 121 ]. In another study, MDRO infections in patients with SBP were associated with the use of antibiotics, including prophylactic antibiotics; hospital-acquired infections; recent history of MDRO infections; recent inpatient care; use of healthcare; and upper gastrointestinal bleeding in patients with liver cirrhosis [ 19 122 123 ].…”
Section: Recommendationsmentioning
confidence: 99%